Năng lực cạnh tranh, lợi nhuận và sự ổn định của các ngân hàng Việt Nam - Võ Xuân , Vinh; Đặng Bửu , Kiếm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This paper investigates the impact of market power on the profit and stability of commercial banks in Vietnam. We employ the data on Vietnamese banks from 2006 to 2014 and the Lerner index to proxy for the bank market power. Employing estimation techniques for the panel data, we find that the increase in market power improves bank profit and bank stability. Other control variables including deposit growth, loan growth, and listing status also affect bank profit and stability.